Bullseye ; Born again - Lazaro, Cheche (The Probe Team, 1988)
Archery as a sport faces controversy when archerer Jo-Ann Chan is eliminated ffrom being a Philippine representative to the Olympics. A look at government's present population program. Features a new Christian revival movement.